Extraction of rare earth elements from fluoride molten salt electrolytic slag by mineral phase reconstruction. (10th March 2018) - Liang, Yong; Li, Yongkang; Xue, Liyan; Zou, Yu
Abstract: There is no environmentally efficient process to extract rare earth elements from the slag of fluoride molten salt electrolysis. An extraction method was developed by drawing on the experience of extracting rare earths from gadolinite by hydrochloric acid decomposition. Sodium silicate roasting was used to reconstruct the phases of the rare earth electrolysis slag in a fluoride molten salt. The rare earth fluoride in the slag was transformed into a rare earth silicate that is easily dissolved by acid. A novel process of extracting rare earths from slag by sodium silicate roasting, washing, and acid leaching was developed. The effects of roasting time, mass ratio of sodium silicate to molten salt electrolytic slag, roasting temperature, leaching time, hydrochloric acid concentration, acid leaching temperature, and leaching liquid–solid ratio on the extraction of rare earths were examined. Under conditions of a roasting time of 1.5 h, roasting temperature of 850 °C, mass ratio of 1.5:1, leaching time of 2 h, hydrochloric acid concentration of 4 mol L -1, leaching temperature of 80 °C, and liquid–solid leaching ratio of 12:1, a leaching efficiency of rare earths from the slag of 98.96% was achieved. Highlights: The LaF3 and LaO0.7 F1.6 in the RE molten salt electrolytic slag were reconstructed to La10 (SiO4 )6 O3 by Na2 SiO3 roasting. The La and F were separated effectively by the process of sodium silicate roasting, washing and acid leaching. The influencing parameters were optimized for the extracting REEs from the rare earth molten salt electrolytic slag. Under the optimum conditions, the extracting efficiency of rare earth can reach as high as 98.96%.